Potential drug–drug interactions of OMBITASVIR, PARITAPREVIR/ritonavir ± DASABUVIR ± ribavirin in clinical practice. Issue 5 (12th February 2018) - González‐Colominas, Elena; Londoño, María‐Carlota; Morillas, Rosa M; Torras, Xavier; Mojal, Sergi; Lens, Sabela; López, Dulce; Gallego, Adolfo; Mariño, Zoe; Ardèvol, Mercè; Pagès, Neus; Solà, Ricard; et al.
Abstract: Background & Aims: Drug–drug interactions (DDIs) with ombitasvir/paritaprevir/ritonavir with or without dasabuvir and with or without ribavirin (OBV/PTV/r ± DSV ± RBV) are common in clinical trials. Our aim was to analyze the prevalence and management of potential DDIs and adverse events (AEs) related to DDIs in patients with chronic hepatitis C (CHC) receiving OBV/PTV/r ± DSV ± RBV in clinical practice. Methods: 177 CHC patients started OBV/PTV/r ± DSV ± RBV in 4 Spanish hospitals and were screened for potential DDIs using the University of Liverpool database. Patients were classified according to the most serious potential DDIs at baseline and AEs during therapy. Results: At least one potential DDI was found in 110 (62.1%) patients: 100 (56.5%) had at least one manageable potential DDI and 10 (5.6%) at least one contraindicated. Patients with potential DDIs were receiving a higher number of concomitant drugs (4 vs. 2, P < 0.001). Routine medication was modified at baseline due to potential DDIs in 49 (27.7%) patients. During antiviral treatment, 67 (37.9%) patients presented at least one AE. In 9 (4.5%) patients, a DDI was suspected between OBV/PTV/r ± DSV ± RBV and the concomitant drug, requiring antiviral discontinuation in 4 patients. Conclusions: Potential DDIs are frequent with OBV/PTV/r ± DSV ± RBV, although a change in baseline medication is made in only one‐quarter of patients. More than half of potential DDIs were only followed, and only 5% of patients developed AEs in which the implication of DDIs could not be excluded.